The role of GST in Promoting Financial Independence among Women Entrepreneurs (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Goods and Services Tax (GST) was implemented in India in July 2017 with the aim of streamlining the taxation system and promoting economic growth. This paper explores the impact of GST on the financial independence of women entrepreneurs. By analyzing secondary data from various sources, including government reports and academic articles, this study examines how GST has influenced business operations, access to credit, and overall financial stability among women-led enterprises. The findings suggest that while GST has simplified tax compliance and improved market access, challenges such as the initial compliance burden and complex filing procedures continue to affect the financial independence of women entrepreneurs.